Accelerating the science and practice of psychology beyond WEIRD biases: Enriching the landscape through Asian psychology - Wong, Paul T. P.; Cowden, Richard G. (Frontiers in Psychology, 2022)
More than a decade has passed since major concerns emerged about the WEIRD-centric focus of mainstream psychological science. Since then, many calls have been made for the discipline of psychology (and other disciplines within the social sciences) to become more broadly representative of the human species. However, recent evidence suggests that progress toward improving the inclusivity and generalizability of psychological science has been slow, and that the dominance of WEIRD psychology has persisted. To build a more comprehensive psychological science that truly represents the global population, we need strategies that can facilitate more rapid expansion of empirical evidence in psychology beyond WEIRD biases. In this paper, we draw on several examples (i.e., non-duality and dialectical interaction, Wu-Wei, Zhong Yong) to illustrate how principles of Asian psychology could contribute to reshaping mainstream psychology. We discuss some strategies for advancing a global psychological science, along with some complementary practical suggestions that could enrich the WEIRD-centric landscape of current psychological science.